Public–private partnership generates economic benefits to smallholder bean growers in Uganda - Aseete, Paul; Barkley, Andrew; Katungi, Enid; Ugen, Michael Adrogu; Birachi, Eliud (Public–private partnership generates economic benefits to smallholder bean growers in Uganda, 2023)
The quest to transform and hasten the role of smallholder farms in agricultural development and food security through farmer-firm linkages has dominated development interventions in low-income countries for several decades. This has mostly been pursued through single- or multi-contract schemes implemented in isolation. Several studies have analyzed the effects of these schemes on smallholder farms with mixed results. A new paradigm is to use Agricultural Public Private Partnership (Ag-PPP) to achieve wider and sustainable impacts. However, limited empirical evidence exists on the effects of Ag-PPP interventions and targeting the same farmer. We address this research gap by assessing the impact of an Ag-PPP on small-scale common bean producers in Uganda. We use a doubly robust difference-in-difference approach in a multi-treatment setting to estimate these impacts. The results show that the PPP created positive outcomes for farmers and stimulated increased production from targeted interventions. Evidence shows that the PPP and its interventions were associated with significant increases in productivity, sales volumes, and shares of output marketed. Receiving bundled interventions had greater effects than a single intervention and effects varied between men and women bean crop owners. Results suggest that providing bundled interventions through a PPP can increase productivity and alleviate market access constraints. The outcomes of this Ag-PPP could be modified for other contexts i.e., crops and localities, to inform food and development policy elsewhere.
Keywords: smallholder farms; agricultural development; food security9; farmer-firm linkages